Seven days in June : a novel - Williams, Tia, 1975- (Grand Central Publishing, 2021)
"Brooklynite Eva Mercy is a single mom and bestselling erotica writer, who is feeling pressed from all sides. Shane Hall is a reclusive, enigmatic, award-winning literary author who, to everyone's surprise, shows up in New York. When Shane and Eva meet unexpectedly at a literary event, sparks fly, raising not only their past buried traumas, but the eyebrows of New York's Black literati. What no one knows is that twenty years earlier, teenage Eva and Shane spent one crazy, torrid week madly in love. They may be pretending that everything is fine now, but they can't deny their chemistry-or the fact that they've been secretly writing to each other in their books ever since. Over the next seven days in the middle of a steamy Brooklyn summer, Eva and Shane reconnect, but Eva's not sure how she can trust the man who broke her heart, and she needs to get him out of New York so that her life can return to normal. But before Shane disappears again, there are a few questions she needs answered. . . With its keen observations of Black life and the condition of modern motherhood, as well as the consequences of motherless-ness, Seven Days in June is by turns humorous, warm and deeply sensual"--